2021
DOI: 10.3390/ijms22105371
|View full text |Cite
|
Sign up to set email alerts
|

Mialostatin, a Novel Midgut Cystatin from Ixodes ricinus Ticks: Crystal Structure and Regulation of Host Blood Digestion

Abstract: The hard tick Ixodes ricinus is a vector of Lyme disease and tick-borne encephalitis. Host blood protein digestion, essential for tick development and reproduction, occurs in tick midgut digestive cells driven by cathepsin proteases. Little is known about the regulation of the digestive proteolytic machinery of I. ricinus. Here we characterize a novel cystatin-type protease inhibitor, mialostatin, from the I. ricinus midgut. Blood feeding rapidly induced mialostatin expression in the gut, which continued after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…This study explores the therapeutic effects of four tick cystatins previously reported for their various immunomodulatory activities and specificity towards key cysteine proteases involved in different pathways related to immunity, inflammation, and homeostasis. Sialostatin L and Sialostatin L2, two cystatins isolated from the salivary glands of Ixodes scapularis ( 15 17 , 23 , 28 31 ), Iristatin, a salivary gland cystatin and Mialostatin, a midgut cystatin were isolated from Ixodes ricinus ( 18 , 19 , 21 ). Table 1 and Supplementary Figure 1 show the protease inhibitors, their primary targets, and published structures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study explores the therapeutic effects of four tick cystatins previously reported for their various immunomodulatory activities and specificity towards key cysteine proteases involved in different pathways related to immunity, inflammation, and homeostasis. Sialostatin L and Sialostatin L2, two cystatins isolated from the salivary glands of Ixodes scapularis ( 15 17 , 23 , 28 31 ), Iristatin, a salivary gland cystatin and Mialostatin, a midgut cystatin were isolated from Ixodes ricinus ( 18 , 19 , 21 ). Table 1 and Supplementary Figure 1 show the protease inhibitors, their primary targets, and published structures.…”
Section: Resultsmentioning
confidence: 99%
“…Mialostatin, a cystatin from the midgut of Ixodes ricinus , inhibits several digestive cysteine-cathepsins, with a high-level potency observed against cathepsin L isoforms. Mialostatin has also effectively blocked in vitro proteolysis of blood proteins by midgut cysteine cathepsins ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Well-documented classical stefins from the type 1 family and true cystatins from the type 2 family are presented, including members of human origin (stefins A and B, cystatins C, D, and F) and those from parasitic ticks (salivary sialostatins L and L2 and iristatin; salivary gland-associated Rhcyst-1; gut-associated mialostatin and OmC2). Inhibition data against various cysteine proteases, including human papain-family cathepsins L to B (hCatL to hCatB) and mammalian legumains, are presented as IC 50 (tick inhibitors ( 10 , 37 , 69 , 70 , 71 ), FhCyLS-2 data are from Table 1 ) or K i values (human inhibitors ( 4 , 72 , 73 , 74 , 75 , 76 )) and colored as a heatmap ( green scale ); n.i. means no inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the examples studied originated from ticks and helminths. In ticks, it was shown that gut-associated cystatins regulate endogenous digestive proteases, while salivary cystatins that are injected into the host can inhibit the secretion of proinflammatory cytokines, reduce T-cell proliferation, or disrupt dendritic cell maturation and differentiation ( 10 , 11 ). Helminth cystatins were demonstrated to block antigen processing and presentation, interfere with the processing of pattern recognition receptors in innate immunity, modulate production of cytokines and nitric oxide, and suppress T-cell proliferation ( 12 , 13 , 14 , 15 , 16 ).…”
mentioning
confidence: 99%
“…In ticks, cystatins have unique properties and functions primarily related to tick feeding and evasion of the host immune response. Tick cystatins are essential for the tick’s ability to feed on the host’s blood and inhibit proteases involved in host immune responses (Karim et al, 2005; Kotsyfakis et al, 2007; Parizi et al, 2020; Lu et al, 2020; Kotál et al, 2021). Similarly, ticks secrete cystatins during tick-borne pathogen infection and colonization.…”
Section: Discussionmentioning
confidence: 99%